Financial history and financial economics - John D. Turner (Queen's University Centre for Economic History (QUCEH), 2014)
This essay looks at the bidirectional relationship between financial history and financial economics. It begins by giving a brief history of financial economics by outlining the main topics of interest to financial economists. It then documents and explains the increasing influence of financial economics upon financial history, and warns of the dangers of applying financial economics unthinkingly to the study of financial history. The essay proceeds to highlight the many insights that financial history can potentially provide to financial economics. The main conclusion of the essay is that financial economics can potentially learn more from financial history than vice versa.
Keywords: G00; N01; N20; 330; financial economics; financial history; asset pricing; agency; corporate finance; behavioural finance; options